IMPLEMENTASI MORAL PANCASILA UNTUK MENGUATKAN WAWASAN KEBANGSAAN ANGGOTA PEMUDA MUHAMMADIYAH : Studi Deskriptif Terhadap Anggota Pemuda Muhammadiyah Di Wilayah Kelurahan Loabakung Kecamatan Sungai Kunjang Kota Samarinda Provinsi Kalimantan Timur - Frenky Zainul Kusyanto, - (2019)
ABSTRACTION This research is entitled "Moral Implementation of Pancasila to Strengthen the National Insight of Muhammadiyah Youth Members in the Territory of Samarinda City Loabakung". The purpose of this study was to describe the implementation of Pancasila morality to strengthen the national insight of Muhammadiyah members in the Loabakung Urban Village of Samarinda City, to find out the obstacles to the implementation of Pancasila morality to strengthen the national insight of members of Muhammadiyah in Samarinda's Loabakung Kunjang Urban Village and to provide solutions to implementation Pancasila morality to strengthen the nationalism of Muhammadiyah youth members in the area of Loabakung Urban Village, Samarinda City. This study used qualitative research methods. The location of this study is the Muhammadiyah branch of the Loabakung Urban Village in Samarinda City. The subjects in this study were Muhammadiyah youth members in the Loabakung Urban Village, Samarinda City. Data collection techniques using interviews, observation, literature studies and documentation studies. Data analysis process with data reduction, data display, and conclusion drawing / verification. ". The results of the study were 2019 political years the Muhammadiyah youth members were divided into two camps, namely the pro money political stronghold and the stronghold still maintained Islamic aqeedah, youth members were busy working activities, difficult to condition the event to be on time, the number of participants was small, it was difficult to get event funds, lack of event organizers. Keywords: Implementation, Moral, Pancasila and National Insight